2016
DOI: 10.1115/1.4034588
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Investigation of Integrated Combustor Vane Concept Under Engine-Realistic Conditions

Abstract: This paper presents a thermal investigation of the integrated combustor vane concept for power generation gas turbines with individual can combustors. This concept has the potential to replace the high-pressure turbine’s first vanes by prolonged combustor walls. Experimental measurements are performed on a linear high-speed cascade consisting of two can combustors and two integrated vanes. The modularity of the facility allows for the testing at engine-realistic high turbulence levels, as well as swirl strengt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Finally, the reductions in the heat transfer coefficient levels are also validated by using Reynold's empirical correlation of the heat transfer in a turbulent boundary layer for a flat plate. An overview of the results presented in this chapter is given by Jacobi and Rosic (2016).…”
Section: Static Pressure Measurementsmentioning
confidence: 99%
“…Finally, the reductions in the heat transfer coefficient levels are also validated by using Reynold's empirical correlation of the heat transfer in a turbulent boundary layer for a flat plate. An overview of the results presented in this chapter is given by Jacobi and Rosic (2016).…”
Section: Static Pressure Measurementsmentioning
confidence: 99%
“…Qureshi et al [16] found that swirl flow changed the vortex pattern and thus the pressure loads distribution of the first stage vane passage. Jacobi et al [17,18] found the swirl flow induces vortices at the leading edge of the vane. Qureshi et al [19,20] found the swirl flow changed the strength of the passage vortex and increased the Nusselt number on both the hub and tip of an airfoil.…”
Section: Introductionmentioning
confidence: 99%
“…Qureshi et al [16] found that swirl flow changed the vortex pattern and thus the pressure loads distribution of the first stage vane passage. Jacobi et al [17][18] found the swirl flow-induced vortices at the leading edge of the vane. Qureshi et al [19][20] found the swirl flow changed the strength of the passage vortex and increase the Nusselt number on both hub and tip of the airfoil.…”
Section: Introductionmentioning
confidence: 99%